LA RELEVANCIA DE TRABAJAR EL USO CRÍTICO Y SEGURO DE INTERNET EN EL ÁMBITO ESCOLAR COMO CLAVE PARA FORTALECER LA COMPETENCIA DIGITAL - Rakel GAMITO GOMEZ,Dra. María Pilar ARISTIZABAL LLORENTE,Dra. María Teresa VIZCARRA MORALES,Alaitz TRESSERRAS ANGULO (Fonseca, Journal of Communication, 2023)
Information and Communication Technologies (ICT) and the Internet have become indispensable means for the daily life of almost sectors of the population. Likewise, digital development has had a great impact on the younger population and, due to the frequent and continuous use of ICT, children are exposed daily to the multiple risks that exist in the network